PROBLEM-SOLVING ASSESSMENT IN MODIFYING TASKS - Subekti, Puji (International Journal of Insights for Mathematics Teaching (IJOIMT), 2019)
An assessment has many benefits, especially in efforts to modify tasks. Often the teacher overrides the process of assessing students in problem-solving. Teachers use easy methods to teach. This causes students only to be able to practice questions and solutions conceptually and cannot develop their creativity in problem-solving. In this study aims to assess prospective teachers to accomplish problem-solving so that they can be creative in modifying tasks for students. The main aspect of this study is to provide an assessment of the problem-solving ability so that prospective teachers can change the new assignment. Students were practicing using an approach to a multi-dimensional perspective SPUR. Can make students excited and try to be creative in modifying the task.